Literatur review: Dukungan nutrisi untuk bayi yang lahir dari ibu dengan Covid-19 - Bakhtiar Bakhtiar (AcTion: Aceh Nutrition Journal, 2020)
COVID-19 suffered by mothers who gave birth has an impact on newborns, including the risk of possible transmission. However, all the needs of newborns must remain a priority, especially regarding protection against possible transmission and nutritional needs, especially breast milk or formula milk. The care of the baby depends on the health condition or the wishes of the mother and family. In mothers with severe COVID-19, babies must be treated separately from their mothers. Conversely, if the mother is asymptomatic, the baby can be treated together, but still according to health protocols. Two impacts on the baby are related to breastfeeding are the risk of transmission and the effects of drugs taken by the mother that can be transmitted through breast milk. There are three ways to provide nutrition for the newborn, depending on the severity of the COVID-19 that the mother is suffering from. If without symptoms, breastfeeding is direct. If symptoms are mild, breastfeeding is indirect. Meanwhile, if COVID-19 with severe symptoms, the baby is only given donor breast milk or formula milk. Provision of advanced nutrition, after treatment, is complete, the baby is still given breast milk from the mother and stops donor breast milk or formula milk.